PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT MANDREHE KABUPATEN NIAS BARAT - Gulo, Andius (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this study was to determine the effect of work motivation and job satisfaction on employee performance at the Mandrehe Sub-district Office, West Nias Regency. The type of research used is quantitative research. The source of the data is from employees, with a population of 31 people and a sample of 31 people. The data collection technique is by distributing questionnaires to respondents, namely employees of the Mandrehe Subdistrict Office, West Nias Regency. The data analysis method used is multiple linear regression analysis. The results of this study show that work motivation (X1) has a significant effect on employee performance (Y) where the work motivation variable (X1) obtained a calculated value (3.355) > table (1.701) and a significance level of 0.002<0.05. Furthermore, for the variable job satisfaction (X2) has a significant effect on employee performance (Y) where the calculated value (2.470) > (1.701) and the level of significance 0.020<0.05 which means that partially the variable job satisfaction (X2) has a significant effect on the employee performance variable (Y). The results of the simultaneous test (Test F), show that the value of Fis calculated (25.769) > Ftable (3.34) and the level of significance is 0.000<0.05, it can be stated that the variables of work motivation (X1) and job satisfaction (X2) silmutant have a positive and significant effect on employee performance variables (Y). For the coefficient of determination (R2) of 0.648, it can be interpreted that work motivation and job satisfaction are only able to explain employee performance variables of 64.8% while the remaining 35.2% is explained by other variables not mentioned by the study. For the result Y=9.543+0.506X1+0.373X2+7.907. So the coefficient (a) of 9.543 is the value of the performance variable when the variables of work motivation and job satisfaction are normal. The regression coefficient for (b1) of 0.506 means that every 1 unit increase in the work motivation variable assuming other variables remain, employee performance will experience 0.506%. Furthermore, the regeneration coefficient for (b2) of 0.373 means that every 1 unit increase in job satisfaction assuming other variables remain, employee performance increases by 0.373%.